2006
DOI: 10.1111/j.1523-5378.2006.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Epithelial Expression of Macrophage Migration Inhibitory Factor is not Altered by Helicobacter pylori Infection in Humans

Abstract: While an increased MIF expression and positive effects of MIF blockade in ulcer healing have been shown in a rodent model and elevated numbers of MIF-positive cells have been found in H. pylori-infected human tissue, we herein could not confirm any differences in human gastric epithelial MIF expression and secretion after H. pylori infection in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The effect was blocked with anti-MIF antibody, suggesting the role of MIF as a mediator of H . pylori -induced tumorigenesis [3437]. The progressive increase of epithelial and serum MIF levels in H .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect was blocked with anti-MIF antibody, suggesting the role of MIF as a mediator of H . pylori -induced tumorigenesis [3437]. The progressive increase of epithelial and serum MIF levels in H .…”
Section: Discussionmentioning
confidence: 99%
“…However, another report suggested that MIF expression and secretion did not directly increase after H . pylori infection, although IL-8 expression and secretion were upregulated [37].…”
Section: Discussionmentioning
confidence: 99%
“…Although H. pylori infection has been reported to increase serum MIF (Xia et al , 2005), other reports have shown little effect of H. pylori on circulating levels of MIF (He et al , 2006; Mohri et al , 2009) and H. pylori infection does not increase expression of MIF in gastric epithelium (Lebiedz et al , 2006). In our study, H. pylori infection appears not to be a contributory factor in raising MIF serum levels (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Xia et al (2005) showed that Hp might stimulate MIF expression, further promoting the proliferation of gastric epithelial cells. However, Lebiedz et al (2006) showed that MIF expression was not related to gastritis mucosa Hp infection and concluded that it had yet to be determined whether Hp infection would stimulate MIF expression and promote gastric mucosal inflammation. Nishihira (2012) suggested that MIF played a significant role in disease and that MIF knockdown could significantly decrease the pathological damage in inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%